An Analysis of Bilateral Trade between India & China Since 2001 - Ahmadi, Mohammad Haroon (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
This research analyzes the existing bi-lateral trade patterns between India and China with a view to locate in the development context. It was essential to analyze the data since 2000 after implementing economic reforms in both countries. This research attempts to analyze the bilateral trade relation between these two countries, and also, focus on strategic frameworks. For determining the export performance, Revealed Symmetric Comparative Advantage (RSCA) method is applied. This study also recommends that trade balance is possible between India and China through making the right policies.